Employee Stock Options, Corporate Taxes, and Debt Policy - Graham, John R.; Lang, Mark H.; Shackelford, Douglas A. (Journal of Finance, 2004)
ABSTRACT We find that employee stock option deductions lead to large aggregate tax savings for Nasdaq 100 and S&P 100 firms and also affect corporate marginal tax rates. For Nasdaq firms, including the effect of options reduces the estimated median marginal tax rate from 31% to 5%. For S&P firms, in contrast, option deductions do not affect marginal tax rates to a large degree. Our evidence suggests that option deductions are important nondebt tax shields and that option deductions substitute for interest deductions in corporate capital structure decisions, explaining in part why some firms use so little debt.